The Recently Discovered Bokeloh Bat Lyssavirus: Insights Into Its Genetic Heterogeneity and Spatial Distribution in Europe and the Population Genetics of Its Primary Host - Eggerbauer, Elisa; Troupin, C.; Passior, K.; Pfaff, Florian; Höper, Dirk; Neubauer-Juric, A.; Haberl, S.; Bouchier, C.; Mettenleiter, Thomas C.; Bourhy, H.; Müller, Thomas; Dacheux, L.; et al. (2017)
In 2010, a novel lyssavirus named Bokeloh bat lyssavirus (BBLV) was isolated from a Natterer's bat (Myotis nattereri) in Germany. Two further viruses were isolated in the same country and in France in recent years, all from the same bat species and all found in moribund or dead bats. Here we report the description and the full-length genome sequence of five additional BBLV isolates from Germany (n = 4) and France (n = 1). Interestingly, all of them were isolated from the Natterer's bat, except one from Germany, which was found in a common Pipistrelle bat (Pipistrellus pipistrellus), a widespread and abundant bat species in Europe. The latter represents the first case of transmission of BBLV to another bat species. Phylogenetic analysis clearly demonstrated the presence of two different lineages among this lyssavirus species: lineages A and B. The spatial distribution of these two lineages remains puzzling, as both of them comprised isolates from France and Germany; although clustering of isolates was observed on a regional scale, especially in Germany. Phylogenetic analysis based on the mitochondrial cytochrome b (CYTB) gene from positive Natterer's bat did not suggest a circulation of the respective BBLV sublineages in specific Natterer's bat subspecies, as all of them were shown to belong to the M. nattereri sensu stricto clade/subspecies and were closely related (German and French positive bats). At the bat host level, we demonstrated that the distribution of BBLV at the late stage of the disease seems large and massive, as viral RNA was detected in many different organs.